DAMPAK CAREER PLATEAU TERHADAP JOB SATISFACTION KARYAWAN GERAI MINIMARKET DI PALEMBANG - EGA LEOVANNI (ANALISIS, 2021)
Various things are done by companies to provide job satisfaction to their employees, one of which is a career path in the company, but not all positions can reach career paths in the company, there are several positions that experience career plates. This study aims to determine the impact of career plateau on job satisfaction of minimarket outlet employees in the city of Palembang. This study uses the independent variable Career Plateau (X), and Job Satisfaction (Y). The data used in this study are primary data. Data collection in this study used a questionnaire method distributed to 150 employees of minimarket outlets in the city of Palembang with a purposive sampling method. While the analysis is done by processing data using SPSS 19.0 for windows. The results of this study indicate that the independent variable Career Plateau (X) has an influence on Job Satisfaction (Y) employees of minimarket outlets in Palembang.